2022
DOI: 10.3390/antibiotics11020249
|View full text |Cite
|
Sign up to set email alerts
|

Significant Difference in Antimicrobial Resistance of Bacteria in Septic Revision between Total Knee Arthroplasty and Total Hip Arthroplasty

Abstract: Antimicrobial resistance (AMR) aggravates the already difficult treatment of periprosthetic joint infections (PJI). Due to many factors influencing AMR, the correct choice of antimicrobial management remains arguable. The primary purpose of this retrospective study was to identify and compare bacteria and their antibiotic resistance profile between septic revision total knee arthroplasty (TKA) and septic revision total hip arthroplasty (THA). A review of all revision TKAs and revision THAs, undertaken between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Our study showed a significant diversity of practice and in many cases a lack of guidance regarding prophylactic antibiotics. The difficulty in establishing such guidelines lies in differences in antibiotic strains over time [ 22 ], between geographic regions and centres [ 23 ] and even hip and knee arthroplasty [ 24 ]. Contribution to guidelines was also heterogenous with only six (35%) explicitly stating multidisciplinary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a significant diversity of practice and in many cases a lack of guidance regarding prophylactic antibiotics. The difficulty in establishing such guidelines lies in differences in antibiotic strains over time [ 22 ], between geographic regions and centres [ 23 ] and even hip and knee arthroplasty [ 24 ]. Contribution to guidelines was also heterogenous with only six (35%) explicitly stating multidisciplinary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that Gram-positive cocci are the most frequently detected pathogens in patients with PJI, the literature is not consistent regarding the role of S. aureus and coagulase-negative staphylococci [ 3 , 12 ]. While Tsai et al identified S. aureus as the most common pathogen with a detection rate of 26%, more recent studies by Hu et al and Stevoska et al identified coagulase-negative staphylococci with detection rates of 38.1 to 56.6% as more common [ 12 , 15 , 17 ]. In accordance with the more recent studies, our most frequently detected pathogens are coagulase-negative staphylococci (44.9%), followed by S. aureus (14.1%), Gram-negative bacteria (13.1%) and Enterococcus species (9.3%).…”
Section: Discussionmentioning
confidence: 99%
“…An additional frequently discussed aspect of PJI is a possible difference of the causative pathogens in patients with PJI of the hip and the knee. While Bjerke-Kroll et al could not detect a difference in the identified species in patients with PJI of the hip or knee, Stevoska et al described a significantly higher rate of Gram-negative bacteria in patients with PJI of the hip [ 14 , 17 ]. As our previous studies did not detect an overall difference in causative pathogens between patients with PJI of the hip and the knee, we did not evaluate this topic [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients meeting other criteria established by the Musculoskeletal Infections Society (MSIS) [ 32 ] were excluded. Due to different rates of PJI depending on the joint to be replaced [ 33 ], a stratification into two groups, THA and UKA/TKA, and an independent analysis was performed.…”
Section: Methodsmentioning
confidence: 99%